Dosimetric validation of a magnetic resonance image gated radiotherapy system using a motion phantom and radiochromic film - Lamb, James M. (J Appl Clin Med Phys, 2017)
PURPOSE: Magnetic resonance image (MRI) guided radiotherapy enables gating directly on the target position. We present an evaluation of an MRI‐guided radiotherapy system's gating performance using an MRI‐compatible respiratory motion phantom and radiochromic film. Our evaluation is geared toward validation of our institution's clinical gating protocol which involves planning to a target volume formed by expanding 5 mm about the gross tumor volume (GTV) and gating based on a 3 mm window about the GTV. METHODS: The motion phantom consisted of a target rod containing high‐contrast target inserts which moved in the superior‐inferior direction inside a body structure containing background contrast material. The target rod was equipped with a radiochromic film insert. Treatment plans were generated for a 3 cm diameter spherical planning target volume, and delivered to the phantom at rest and in motion with and without gating. Both sinusoidal trajectories and tumor trajectories measured during MRI‐guided treatments were used. Similarity of the gated dose distribution to the planned, motion‐frozen, distribution was quantified using the gamma technique. RESULTS: Without gating, gamma pass rates using 4%/3 mm criteria were 22–59% depending on motion trajectory. Using our clinical standard of repeated breath holds and a gating window of 3 mm with 10% target allowed outside the gating boundary, the gamma pass rate was 97.8% with 3%/3 mm gamma criteria. Using a 3 mm window and 10% allowed excursion, all of the patient tumor motion trajectories at actual speed resulting in at least 95% gamma pass rate at 4%/3 mm. CONCLUSIONS: Our results suggest that the device can be used to compensate respiratory motion using a 3 mm gating margin and 10% allowed excursion results in conjunction with repeated breath holds. Full clinical validation requires a comprehensive evaluation of tracking performance in actual patient images, outside the scope of this study.